2021
DOI: 10.1016/j.amjoto.2021.103102
|View full text |Cite
|
Sign up to set email alerts
|

Early vs. late tracheostomy in ventilated COVID-19 patients – A retrospective study

Abstract: Background Tracheostomy is one of the most common surgical procedures performed on ventilated COVID-19 patients yet the appropriate timing for operating is controversial. Objectives Assessing the effect of early tracheostomy on mortality and decannulation; elucidating changes in ventilation parameters, vasopressors and sedatives dosages immediately following the procedure. Methods A retrospective cohort of 38 ventilated COVID-19 patients, 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
3
18
2
Order By: Relevance
“…Comparing our results with the ones found in the literature, Livneh et al 20 reported 38 tracheostomies performed on a series of cases, similar with our study, in the same period of time, with a male gender dominance of 87% versus 80.65% in our case, while in Reis et al 21 study, performed between 2020-2021 on 42 patients with SARS-CoV-2, 71% of the patients were males. The mean age of the patients included in these two studies was 57.1±13,395 years (range 56-72) in Livneh et al and 68.4±11.1 years (range 47-90) in Reis et al study 20,21 . With respect to the time of IOT, in our series it was of 20.52±6.722 days (range 11-43), higher compared to the time reported by Livneh et al with 16 days 20 , but similar to the results of Reis et al of 22.9±6.5 days 21 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Comparing our results with the ones found in the literature, Livneh et al 20 reported 38 tracheostomies performed on a series of cases, similar with our study, in the same period of time, with a male gender dominance of 87% versus 80.65% in our case, while in Reis et al 21 study, performed between 2020-2021 on 42 patients with SARS-CoV-2, 71% of the patients were males. The mean age of the patients included in these two studies was 57.1±13,395 years (range 56-72) in Livneh et al and 68.4±11.1 years (range 47-90) in Reis et al study 20,21 . With respect to the time of IOT, in our series it was of 20.52±6.722 days (range 11-43), higher compared to the time reported by Livneh et al with 16 days 20 , but similar to the results of Reis et al of 22.9±6.5 days 21 .…”
Section: Discussionsupporting
confidence: 91%
“…The mean age of the patients included in these two studies was 57.1±13,395 years (range 56-72) in Livneh et al and 68.4±11.1 years (range 47-90) in Reis et al study 20,21 . With respect to the time of IOT, in our series it was of 20.52±6.722 days (range 11-43), higher compared to the time reported by Livneh et al with 16 days 20 , but similar to the results of Reis et al of 22.9±6.5 days 21 . Among the factors associated with death, some comorbidities such as heart disease and age over 60 years are described.…”
Section: Discussionmentioning
confidence: 82%
“…Thirteen studies [ 21 – 23 , 31 33 , 35 41 ] provided data on overall mortality. Mortality was reported at 30 days following tracheostomy [ 33 ], at 30 days following ICU admission [ 32 , 35 ], at 60 days following intubation [ 39 ], at ICU [ 21 , 40 , 41 ] and hospital discharge [ 23 , 31 , 36 , 38 ] and at an undefined time point [ 22 , 37 ]. Moderate statistical heterogeneity was detected ( I 2 = 41%).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [ 21 , 23 , 32 , 36 38 ] provided data on time from tracheostomy to ventilator weaning. Ventilator weaning was not defined in two studies [ 23 , 37 ] and was defined in four studies as discontinuation of mechanical ventilation [ 21 , 32 , 36 , 38 ]. Low statistical heterogeneity was detected ( I 2 = 30%).…”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with data reported from previous studies [ 18 , 32 , 33 ]. The optimal timing for tracheostomy provided conflicting evidence [ 13 , 14 , 15 , 16 , 21 , 34 , 35 ]. In our study, longer ICU stay was found in the TS group.…”
Section: Discussionmentioning
confidence: 99%